The Role of Zakat Infaq & Alms In The Field of Health: Analysis of Social Return On Investment In Desa Bebas Stunting Program - Nonica Hidayati; Abdussalam; Aditya Rahmat Gunawan (Media Gizi Indonesia, 2026)
Stunting is a chronic nutritional problem that has a broad impact on the health and quality of human resources. To overcome it, effective and collaborative interventions are needed. Rumah Zakat as an Islamic philanthropic institution initiated the Desa Bebas Stunting Program to accelerate stunting mitigation through a community empowerment approach. This study aims to measure the impact of the program using the Social Return on Investment (SROI) method in Tegaren Village. The study was conducted using a mixed-method method, combining qualitative and quantitative approaches through focus group discussions, in-depth interviews, and document studies. The SROI ratio was calculated based on the Net Present Value of Benefit and Net Present Value of Investment. The results of this study showed that based on the SROI calculation, it produced a ratio of 1:2.2, meaning that every IDR 1 investment produced IDR 2,2 in social benefits. This finding showed that the program had a significant impact on beneficiaries, cadres, and the community, and was effective as a community empowerment program in reducing stunting rates. This study also contributed to the development of theories regarding the effectiveness of the distribution of zakat, infaq, and alms as instruments of Islamic philanthropy in creating sustainable social impacts and community empowerment.